2006
DOI: 10.1074/jbc.m604960200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the RUN Domain of the RAP2-interacting Protein x

Abstract: Rap2-interacting protein x (RPIPx) is a homolog of RPIP8, a specific effector of Rap2 GTPase. The N-terminal region of RPIP8, which contains the RUN domain, interacts with Rap2. Using cell-free synthesis and NMR, we determined that the region encompassing residues 83-255 of mouse RPIPx, which is 40-residues larger than the predicted RUN domain (residues 113-245), is the minimum fragment that forms a correctly folded protein. This fragment, the RPIPx RUN domain, interacted specifically with Rap2B in vitro in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…The RUN domain was originally found in a group of proteins that interact with small GTPases (15)(16)(17). It was therefore proposed as a binding surface for small GTPases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RUN domain was originally found in a group of proteins that interact with small GTPases (15)(16)(17). It was therefore proposed as a binding surface for small GTPases.…”
Section: Discussionmentioning
confidence: 99%
“…Rubicon is involved in autophagosome maturation and is likely involved in endosome maturation also (9,10). Rubicon contains 972 amino acids, with a coiled-coil domain, an FYVE-like domain, and a recognizable RUN domain that is shared by a group of proteins interacting with small GTPases (15)(16)(17).…”
Section: Composition Of the Rubicon-containing Pi3kc3 Complex-mentioning
confidence: 99%
“…S1B). Moreover, the minimal Rap2-binding site of RUFY3 has been shown to be 40 amino acids larger than the predicted RUN domain (Kukimoto-Niino et al, 2006), indicating that the RUN domain alone is insufficient to recognize Rap2. This observation is very similar to our own results showing that the minimal Rab35-binding site of RUSC2 is larger than the predicted RUN domain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is still an open question, because our findings clearly rule out the possibility that Rab is a common ligand of all RUN domains. Since some RUN domains have been shown to bind Rap, another type of small GTPase (Janoueix- Lerosey et al, 1998;Kukimoto-Niino et al, 2006;Yang et al, 2007), Rap may be a common ligand of RUN domains. However, we think that this possibility is also unlikely because of the very low sequence conservation among the known RUN domains (only one Tyr residue is invariant in all RUN domains; asterisk in Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Recently, the crystal structure of its RUN domain was reported (30). We designated it singar1, together with Dr. Osamu Ohara (Kazusa DNA Research Institute), who initially reported its full cDNA sequence as KIAA0871 (AB020678) and Dr. Takahiro Nagase (Kazusa DNA Research Institute).…”
Section: Identification Of Singar1 By a Proteome Screening Of Stage 2mentioning
confidence: 99%